The effects of time-variance on impedance measurements: examples of a corroding electrode and a battery cell - Nicolas Murer; Jean-Paul Diard; Bogdan Petrescu (Journal of Electrochemical Science and Engineering, 2020)
When performing electrochemical impedance spectroscopy (EIS) measurements on a system, we must make sure it fulfills certain conditions. One of them is that it should be stationary that is to say, steady-state and time-invariant. Commonly studied systems are time-variant, for example a corroding electrode or a battery under operation. A corroding electrode sees its polarization resistance decrease with time. A passivating electrode sees its polarization resistance increase with time. These phenomena cause a deformation of the Nyquist impedance at low frequencies. This result was first simulated and validated by experimental measurements on a corroding steel sample undergoing uniform corrosion. The effect of performing impedance measurements on a discharging battery was also shown. Several methods are available to check and correct time-variance. The non-stationary distortion (NSD) indicator is used to separate valid and invalid data samples and the so called “4D impedance” method can easily produce instantaneous impedance data.